Anything goes? Recognising norms, leadership and moderating behaviours at folk clubs in England. Issue 3 (2nd September 2019) - Hield, Fay; Mansfield, Paul
ABSTRACT: Understanding the behavioural norms at folk clubs in England is complex because their rules of operation are rarely explicit. It is unclear how singers acquire the appropriate skills for successful engagement, and how rule management works within a musical community that prides itself on following egalitarian principles is unknown. Data from four fieldwork projects between 2008 and 2018 is combined with the authors' experience as long term participants to trace how folk clubs in England operate, with an emphasis on how normative patterns of musical behaviour are established and maintained. We found variations in how explicit folk clubs are about stating what music may be performed and how the performance context is structured. Concepts of accepted repertoire and membership show that appropriateness is incrementally learned, alongside generating a sense of belonging. This process of developing cumulative norms makes explicit rule making difficult, resulting in moderating behaviours that are correspondingly complex. As a result, opaque techniques such as humour, sarcasm or avoidance are applied. The projected images of openness and inclusiveness disguise the extent to which various forms of power operate in the range of musical experiences available within the same folk club tradition.